The Ethics of Ability and Enhancement (Jepson Studies in Leadership, 2018)
This book explores our ethical responsibilities regarding health in general and disabilities in particular. Disability studies and human enhancement stand out as two emerging areas of research in medical ethics, prompting debates into ethical questions of identity, embodiment, discrimination, and accommodation, as well as questions concerning distributive justice and limitations on people's medical rights. Edited by two ethicist philosophers, this book combines their mastery of the theoretical debates surrounding disability and human enhancement with attention to real world questions that health workers and patients may face. By including a wide range of high-quality voices and perspectives, the book provides an invaluable resource for scholars who are working on this important and emerging area of leadership and health care ethics. .